Pemodelan Perpindahan Massa Adsorpsi Zat Warna pada Adsorben Berbasis Jatropha Curcas L. dengan Homogeneous dan Heterogeneous Surface Diffusion Model - Aditya Putranto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
The major objective of this experiment is to assess applicability of surface diffusion model to model the adsorption of methylene blue into Jatropha Curcas L. based adsorbents. Homogeneous Surface Diffusion Model (single pore consideration) and Heterogeneous Surface Diffusion Model (multi pore consideration) will be used in this modelling experiments. The modelling data were estimated and validated based on the published experimental results. Subsequently, simulation will be conducted by establishing three dimensional profile of solid phase concentration vs. radius and adsorption time. This simulation was held to discover and observe the adsorbent performance. The other objectives in this modelling experiment are to verify the model’s accuracy against the mass transfer phenomena of the following adsorption process.Based on the modelling experiment, Homogenous Surface Diffusion Model doesn’t fit to show mass transfer characteristic for adsorption based on Jatropha Curcas L. press-cake residue. However, Heterogeneous Surface Diffusion Model is perfectly appropriate to show the mass transfer characteristic. Hence, the validation and simulation will be done only to the appropriate model. Based on mathematics model, effective diffusivity coefficient () and the rate diffusivity coefficient () are either affected by initial solution’s concentration of methylene blue or the type of adsorbent.